Condensed tannin reactivity inhibition by internal rearrangements: Detection by CP-MAS 13C NMR - Navarrete, P.; Pizzi, A.; Bertaud, F.; Rigolet, S. (Maderas. Ciencia y Tecnología, 2025)
Tannin extracts were prepared from barks of maritime pine (Pinus maritimus), aleppo pine (Pinus halepensis), Norway spruce (Picea abies) and from a mixture of barks of different pine species (Pinus spp., namely 20% black pine (Pinus thunbergii)+ 30% Scots pine (Pinus sylvestris) + 20% maritime pine (Pinus maritimus) + 10% Aleppo Pine (Pinus halepensis) + 5% Douglas fir (Pseudotsuga menziesii) + 15% Norway spruce (Picea abies)) at a paper mill. The 13C-NMR spectra were carried out from these tannins. Blending systems adhesives were prepared with 5% paraformaldehyde to measure the reactivity by gel time, and to determinate the mechanical resistance by thermomechanical analysis (TMA) and the internal bond strength (IB) according to the European Norm EN-312. The CP MAS 13C NMR bands at 163 ppm and the increase number of smaller bands between 20 and 65 ppm clearly indicate that the extraction of procyanidin-type tannins has been incorrect yielded high relative proportions of catechinic acid structures and diarylpropanol-catechinin acid dimer caused by internal flavonoid rearrangement, and causing the blockage of the C6 and C8 reactive sites, rendering unusable the tannin for wood adhesive applications. Thus, the gel times are very long except for the maritime pine tannin with a value of 51 (s). The TMA analysis gave very low MOE values for almost all the tannin extract samples, except for maritime pine. This situation was confirmed by the IB test. Only maritime pine tannin presented a good mechanical resistance with a value of 0.6 (MPa). Only this sample fulfils the standard requested.